Workshop on Massive Production of HYV of Rice under Rainfed Condition in Bangladesh, 15th and 16th May 1974 (Bangladesh Rice Research Institute, 1974)
Papers and recommendations of a seminar on high yielding varieties of rice in Bangladesh.